What Are the GDPR Requirements for Healthcare AI? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence (AI) in healthcare presents transformative opportunities, from diagnostics to personalized treatments. However, th...
Keywords: Healthcare Data Privacy and Security; Requirements; Healthcare; Artificial Intelligence; Diagnostics